Elizabeth Spencer : novels & stories - Spencer, Elizabeth, 1921-2019 (Library of America, 2021)
Over the course of a career that spanned six decades, the southern novelist and short story writer Elizabeth Spencer established herself as one of the finest literary artists of a generation that included Flannery O'Connor, Carson McCullers, and Eudora Welty. This definitive volume brings together three remarkable novels: The Voice at the Back Door, her powerful masterpiece about racial politics in the world of Jim Crow Mississippi; the beloved classic The Light in the Piazza, a celebration of the possibilities of love set amidst the splendors of Florence; and its "dark companion," Knights and Dragons, about a woman working in Rome who is obsessed with the enigmatic specter of her ex-husband. A selection of nineteen stories reveals Spencer, as Richard Ford writes, as "a rare and true master" of the form.